PRE-RODINIAN (MESOPROTEROZOIC) SUPERCONTINENTAL RIFTING ALONG THE WESTERN MARGIN OF LAURENTIA: GEOCHEMICAL EVIDENCE FROM THE BELT-PURCELL SUPERGROUP - Luepke J.J.; Lyons T.W. (My University, 2001)
Recent efforts at supercontinental reconstruction for the late Precambrian (e.g., the SWEAT hypothesis Moores, 1991) have commonly invoked an uncertain lacustrine interpretation for deposition of the Mesoproterozoic Belt-Purcell Supergroup, with the Belt basin placed centrally within the assembled landmass. The utility of the Belt-Purcell system in addressing Proterozoic continental configurations has improved with refined constraints on the timing and setting of deposition. Contrary to a lacustrine interpretation, elemental carbon-sulfur (C-S) relationships and stratigraphic S isotope trends for black shales of the Helena Embayment of western Montana, the easternmost extension of Belt deposition, reveal that the early Belt basin received at least episodic fluxes of open marine water into a variably restricted setting. In the present study, this model of restricted marine deposition was tested and corroborated by generation of an analogous S isotope stratigraphy for the time equivalent Prichard Formation, located to the west of the embayment within the main Belt basin. Data for both pyrite and coexisting pyrrhotite show comparatively high δ34S values and systematic S isotope shifts in excess of 20%% over stratigraphic intervals spanning several hundred meters, suggesting limited and temporally varying sulfate availability in a bacterially driven marine system. Additional geochemical and sedimentological proxies (e.g. δ13C of carbonate lithologies, diagnostic abiotic carbonate precipitates, and the presence of glauconite) further support a repeated or continued marine linkage throughout Belt deposition. A model for a restricted marine setting, when viewed in light of independent tectonic evidence (i.e. syndepositional mafic magmatism with peaks in activity at approximately 1470 and 1370 Ma; hydrothermal activity/mineralization along basin-bounding, high-angle normal faults; and high rates of sedimentation that resulted in sediment thicknesses of up to ~16 km) defines a history of active and likely episodic rifting for the Belt basin. Collectively, these observations are temporally consistent with new models for Precambrian supercontinent cyclicity and suggest a complex history for western Laurentia that includes both episodes of convergence and at least incipient rifting prior to the final assembly of Rodinia. This relationship reflects a stepwise continental assembly perhaps analogous to the formation of Gondwana and the subsequent assembly of Pangea.
Keywords: MESOPROTEROZOIC; SULFIDE; ISOTOPE GEOCHEMISTRY; BELT SUPERGROUP; SUPERCONTINENT; Precambrian::Proterozoic::Mesoproterozoic; Докембрий::Протерозой::Мезопротерозойская